Rancang Bangun Sistem Monitoring Kualitas Air bersih Pada Konsumen PERUMDA Tirta Pakuan Bogor Berbasis Web - Rasya, Raihannissa Hatridininar; Hardianto, Joko; Siskandar, Ridwan (PUSAT SAINS INDONESIA, 2020)
System monitoring water clean quality with for pH value measurement, turbidity and temperature water DS18B20. Process control pH Give Limits that refer to the Ministry of Health's standard table and the pH data can be tested in a laboratory to check its accuracy. The purpose of making this system is to monitor the quality of filled water using the third sensor which is combined with Arduino Uno microcontroller. And to make it easier for consumers to monitor the water obtained. This tool can be monitored through the web in the form of datalog and graphic values ​​in realtime.